IMPLEMENTASI DAN EFEKTIVITAS KEBIJAKAN PEMERINTAH DALAM BENTUK BANTUAN PANGAN NON TUNAI TAHUN 2020 DI KECAMATAN SORKAM KABUPATEN TAPANULI TENGAH - Juan Apri Sihombing (Magister Hukum Universitas HKBP Nommensen, 2022)
One of the programs established by the government to reduce the burden on the community in meeting basic needs is the Non-Cash Food Assistance Program (BPNT). This study aims to determine the implementation of the Non-Cash Food Assistance Program (BPNT) in Sorkam District, Central Tapanuli Regency. This research is a qualitative descriptive study. Data collection techniques used are observation, interview, and documentation techniques. Determination of informants using purposive sampling technique. The data validity technique used is triangulation. The results of the research regarding the Implementation of the Non-Cash Food Assistance Program (BPNT) in Sorkam District, in Interorganizational Communication; The socialization carried out by the implementing actors has been carried out properly and sustainably, namely before the launch of the BPNT program through E-Warong in Sorkam District and monthly socialization by the companion party to the target group. Implementing Characteristics; The process of implementing the BPNT policy in Sorkam District has been optimal and is felt by the community. However, the behavior of implementing agents in service still needs to be improved. Social, economic and political conditions; the social situation is still not good because there are still some residents who are illiterate so that in conducting transactions the BPNT program has difficulty. For the economic situation of the community can still be said to be stable and the political situation in Indonesia is also not experiencing problems. The disposition or attitude of the executor; implementor that the parties involved provide a good response to the implementation of the BPNT program which will later be able to achieve its goals properly. All the implementers involved have actually carried out their respective tupoksi, it's just that there are implementors who are reluctant to carry out their duties.